Conformational analysis of argiopine molecule obtained from Argiope lobata spider venom - Godjayev, Niftali M.; Aliyeva, Irade N.; Aliyev, Cevanşir I.; AKYÜZ, SEVİM (Elsevier, 1995)
The conformational behavior of argiopine, the molecule that blocks the glutamate-activated ion channels of the central nervous system in mammals, was investigated by theoretical conformational analysis. Realization of two types of structures, i.e. the pseudocyclic structure, formed by the hydrogen bonds between residues at the opposite ends of the molecule, and the entirely stretched-out structure, were shown to be possible for an isolated molecule. The molecular structure of argiopine essentially depends on the conditions in which the molecule functions.